Congenital toxoplasmosis as a relevant health problem - Kapka, Lucyna; Perżyło, Katarzyna; Cyranka, Małgorzata; Skrzypczak, Maciej; Wdowiak, Leszek (Polish Journal of Public Health, 2010)
Toxoplasma gondii is an intracellular protozoan parasite. It is common worldwide among warm-blooded animals and can be transmitted to humans causing zoonosis. It is estimated that every third person in the world is infected. In Poland 50-60% people are infected. Toxoplasma gondii is an important cause of clinical disease in fetuses, infants and immunocompromised patients. It is one of the most frequent parasitic infections, especially dangerous in congenital form and in people with immunologic deficiency.Congenital infections can result in progressive damage, most commonly to the brain, ocular lesions and retina in prenatal development and heighten the risk of neurological and visual impairment in newborn. Congenital toxoplasmosis results from transplacental transmission of Toxoplasma gondii infection. The incidence and the severity of congenital infection vary with the time of infection (incidence in 1st trimester: 15-20%; incidence in 3rd trimester: 65%). In case of early transmission in pregnancy, neurological abnormalities may lead to severe malformation or stillbirth. The diagnosis relies mainly on serology. The tests for toxoplasmosis are based on measurement of specific anti-Toxoplasma IgG and IgM antibodies with automated tests. However, none of these tests reliably determine the timing of parasitaemia on gestation.T. gondii infection has important implications for public health, since it affects one-third of the world’s population and causes disease, miscarriage or congenital malformations. Health demand for strategies against toxoplasmosis remains strong as well as early postnatal diagnosis of infection in neonate and developing new tests for maternal infection timing.This article summarizes the information about the T. gondii infection problem and suggests possible actions and prevention strategies against toxoplasmosis, especially congenital toxoplasmosis.